Self-Efficacy of Class X Students on The Material of The Three-Variable Linear Equation System - Wahyuningsih, Widya Pri (Integral (Jurnal Penelitian Pendidikan Matematika), 2024)
This study aims to determine the level of self-efficacy of students in the material of the Three-Variable Linear Equation System (SPLTV). The method used in this study is descriptive research with a qualitative approach. The subjects in this study are students of class X of Al-Irsyad High School, Tegal City, which totals 31 students. The data collection technique in this study is in the form of providing a questionnaire using the Likert Scale. The results of this study show that students have high self-efficacy in the material of the Three-Variable Linear Equation System (SPLTV) as seen from the answers to the statements in the questionnaire